PLANT POWER: HARNESSING THE HEALING POTENTIAL OF PHYTOCHEMISTRY - Aamir Sultan Lone (Jurnal Mahasiswa Agribisnis, 2023)
Phytochemistry explores the chemical compounds produced by plants, known as phytochemicals, which serve various functions, including defense against pathogens and pests. Phytochemicals encompass a diverse range of structures and classifications, such as amino acids, phenolics, terpenoids, alkaloids, and organosulfur compounds. These compounds have been utilized in traditional medicines for centuries and exhibit potential therapeutic applications for metabolic, immunological, and neurological disorders. This article examines key examples of phytochemicals and their associated therapeutic properties, including curcumin, resveratrol, quercetin, ginkgolides, and berberine. Moreover, it discusses the mechanisms by which phytochemicals interact with the human body at cellular, molecular, metabolic, and systemic levels, modulating physiological and pathological processes. The study highlights recent advancements in phytochemical research, such as in silico and in vitro approaches, nanotechnology and drug delivery systems, phytochemomics and metabolomics, as well as phytopharmacology and clinical trials. Integrating traditional knowledge with modern scientific approaches is essential in harnessing the healing potential of phytochemistry, ensuring sustainable and culturally sensitive practices in natural product research and development. Keywords: alkaloids, biosynthetic, classification, phytochemicals, therapeutic applications